Penerapan Strategi Giving Question and Getting Answers untuk Meningkatkan Hasil Belajar Siswa Sekolah Dasar Negeri - Dina Istiqomah; Sonita Yulianti (ARZUSIN, 2025)
The low academic performance of fifth-grade students in Social Studies at SDN 016 Balung—where only 44% met the Minimum Mastery Criteria (KKM)—along with limited interest, participation, and confidence during lessons, served as the background for this study. The research aims to improve learning outcomes through the implementation of the active learning strategy Giving Question and Getting Answers (GQGA), which positions students as active agents in the learning process. A Classroom Action Research (CAR) design was employed over two cycles within one month, using observation, tests, and documentation for data collection. Data were analyzed using descriptive quantitative methods to evaluate improvements in teacher activity, student activity, and learning outcomes. The findings indicate substantial improvement: teacher activity increased from 66.07% (fairly good) in the first cycle to 89.28% (good) in the second cycle; student activity rose from 69.42% to 89.14%; and student mastery improved from 44% (pre-intervention) to 60% in the first cycle and 88% in the second cycle. These results demonstrate that the GQGA strategy effectively enhances student engagement and academic achievement in Social Studies. It is therefore recommended as an alternative active learning approach that fosters optimal and sustained student involvement in primary education.